2015
DOI: 10.1016/j.ijheh.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Associations between urinary phenol and paraben concentrations and markers of oxidative stress and inflammation among pregnant women in Puerto Rico

Abstract: Phenols and parabens are used in a multitude of consumer products resulting in ubiquitous human exposure. Animal and in vitro studies suggest that exposure to these compounds may be related to a number of adverse health outcomes, as well as potential mediators such as oxidative stress and inflammation. We examined urinary phenol (bisphenol A (BPA), triclosan (TCS), benzophenone-3 (BP-3), 2,4-dichlorophenol (24-DCP), 2,5-dichlorophenol (25-DCP)) and paraben (butyl paraben (B-PB), methyl paraben (M-PB), propyl p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 192 publications
(121 citation statements)
references
References 40 publications
3
112
1
Order By: Relevance
“…Tier 2 included 13 publications. Twelve of those publications (Wolff et al , 2010(Wolff et al , 2015Philippat et al 2012Philippat et al , 2014Watkins et al 2015;Aker et al 2016;Ashley-Martin et al 2016;Buckley et al 2016;Lassen et al 2016;Smarr et al 2017;Geer et al 2017) were based on seven different cohorts assembled in France, Puerto Rico, Denmark, Canada, and various parts of the US. One paper ) presented a case-control study that used incident cases identified among members of a French cohort.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Tier 2 included 13 publications. Twelve of those publications (Wolff et al , 2010(Wolff et al , 2015Philippat et al 2012Philippat et al , 2014Watkins et al 2015;Aker et al 2016;Ashley-Martin et al 2016;Buckley et al 2016;Lassen et al 2016;Smarr et al 2017;Geer et al 2017) were based on seven different cohorts assembled in France, Puerto Rico, Denmark, Canada, and various parts of the US. One paper ) presented a case-control study that used incident cases identified among members of a French cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 43 studies, 24 were conducted in North America (Wolff et al , 2010(Wolff et al , 2015Clayton et al 2011;You et al 2011;Buttke et al 2012;Savage et al 2012Savage et al , 2014Koeppe et al 2013;Lankester et al 2013;Buser et al 2014;Spanier et al 2014;Adgent and Rogan 2015;Li et al 2015;Ihde et al 2015;Shiue 2015aShiue , 2015bVelez et al 2015;Ashley-Martin et al 2016;Buckley et al 2016;Poole et al 2016;Scinicariello and Buser 2016;Smarr et al 2017;Geer et al 2017), two studies in the Caribbean (Watkins et al 2015;Aker et al 2016), 10 studies in Europe (Allmyr et al 2009;Chevrier et al 2012;Philippat et al 2012Philippat et al , 2014Bertelsen et al 2013;Buhl et al 2014;Den Hond et al 2013, 2015Geens et al 2015;Lassen et al 2016), four in Asia (Chen et al 2013;Wang et al 2015;Xue et al 2015;Zhu et al 2016), and three in Australia (Cullinan et al 2012(Cullinan et al , 2015a…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations